CORRELATION BETWEEN ENGLISH ABILITY AND EMPLOYEE’S PERFORMANCE AT PT. PELINDO JASA MARITIM MAKASSAR - Azizah, Fauziah; Sunusi, Seny Luhriyani; Sakkir, Geminastiti (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This research aims to find out what is their correlation and positive influence between English ability and employee’s performance in the workplace. This research uses a quantitative, type of correlational research to find whether or not there is a correlation and, if there is, how close the correlation is, and whether it means or does not. The data obtained is then processed using statistical analysis which uses SPSS. Data collection techniques used questionnaires, data collection with questionnaires is carried out by asking questions to respondents. The result of this study shows that there a correlation and positive influence between English ability and employee’s performance. The indicators from variable X were reading, listening, speaking, writing and the indicators from variable Y was Job completion, contribution and discipline. The correlation coefficient ranges from -1 to 1, where 1 signifies a perfect positive correlation. In this case, the value of 0.780 suggests a highly positive correlation between the two variables. From the results obtained from several tests that have been verified as valid, this result significantly strengthens the hypothesis (H1) that there is a positive association between English ability and employee performance. In statistical terms, the correlation coefficient being close to 1 provides strong evidence supporting the acceptance of our hypothesis. It implies that as English ability increases, employee performance tends to improve.